2014
DOI: 10.1186/1471-2458-14-1015
|View full text |Cite
|
Sign up to set email alerts
|

NHS patients, staff, and visitor viewpoints of smoking within a hospitals’ ground: a qualitative analysis

Abstract: BackgroundSmoking is a public health concern and an avoidable cause of morbidity and mortality. Widening tobacco control policies might help shift social norms, the acceptability of exposing others to second-hand smoke, and cultural attitudes towards smoking. This study explored patient, staff, and visitor viewpoints of smoking within the grounds of a National Health Service hospital.MethodsAnalysis of free text responses given as part of a larger repeat cross sectional questionnaire study. Free text qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Creating smoke-free environments denormalises tobacco use and supports increased quitting, but the presence of smokers at a busy hospital entrance undermines this public health message. 9,[18][19][20] Our data indicated the broadcasts of children voicing smokefree messages made the entrance a less appealing environment for F I G U R E 2 Daily summary of cigarettes/hr (bars), nonsmoker movements (solid line) and daytime temperature smoking, but frequency of messaging was important for significant effect. The original study design had 5-minutely broadcast intervals, but this plan occurred before the recording workshop, and the final sound bites obtained were shorter than anticipated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Creating smoke-free environments denormalises tobacco use and supports increased quitting, but the presence of smokers at a busy hospital entrance undermines this public health message. 9,[18][19][20] Our data indicated the broadcasts of children voicing smokefree messages made the entrance a less appealing environment for F I G U R E 2 Daily summary of cigarettes/hr (bars), nonsmoker movements (solid line) and daytime temperature smoking, but frequency of messaging was important for significant effect. The original study design had 5-minutely broadcast intervals, but this plan occurred before the recording workshop, and the final sound bites obtained were shorter than anticipated.…”
Section: Discussionmentioning
confidence: 88%
“…Debate may occur on the value of such projects that use children's voices to potentially shame and stigmatise unwell people who smoke in health care setting, particularly those where assessment and treatment of tobacco dependency is suboptimal. Most would agree that smoking in the shared environment of a hospital entrance smoking is highly undesirable and difficult to manage, [18][19][20] so further research on ways to minimise is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…The survey investigated self-reported actual and perceived social norms associated with smoking in hospital entrances and on hospital grounds. Serafin et al reported the results of the secondary analysis of the free text responses provided by participants [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The introduction and implementation of the smokefree legislation in England in 2007 has had public health benefits by helping smokers to quit, reducing cigarette consumption and smoking prevalence [ 6 ]. While the national smoking ban inside buildings is understood and adhered to, there is a perception this has led to staff, patients and visitors smoking at hospital entrances and within hospital grounds [ 14 , 15 ]. Unintended consequences of smoking bans that inadvertently see a concentration of smokers at entrances or perimeters remain a public health concern [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…31e33 Smoking at entrances may give visitors a poor impression, increase smoking debris, and undermine the message of an SFP. 31,34 It is therefore important to identify solutions to resolve this recurrent problem. Previous studies have suggested expanding SFPs to entrance areas.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%